Visual Analysis On A Balinese Kampung Style Gastronomy Attraction: Perceptions Of Indonesian And Chinese Youngsters - Rimalinda Lukitasari; I Gusti Ayu Ari Agustini; Vivi Vivi; Fang Jie (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2026)
Visual perception plays a decisive role in how consumers interpret culinary identities, especially in gastronomy destinations that rely heavily on aesthetic cues. This study examines how Nasi Tekor, a Balinese kampung-style gastronomy attraction, is perceived through visual stimuli presented to millennials and Gen Z consumers from Indonesia and China who have never visited the venue. Using a qualitative visual analysis combined with semiotic interpretation, the research assesses how individuals decode curated images sourced from field observations and social media posts. Findings show that consumers’ perceptual responses are strongly shaped by key visual cues, including banana-leaf plating, bamboo utensils, rustic wooden structures, woven crafts, and traditional attire. These elements are consistently processed as indicators of authenticity, nostalgia, and cultural rootedness, forming a brand image that aligns with heritage-based gastronomy. However, modern furniture and semi-modern design features create perceptual dissonance, leading some participants to interpret the visuals as inconsistent or less authentic. The results also highlight that visual perception on digital platforms influences not only emotional reactions but also functional judgments related to hygiene, comfort, and clarity of menu offerings. Overall, this study demonstrates that visual perception is central to shaping brand meaning, moreover, a coherent visual communication is essential for reinforcing Nasi Tekor’s identity across both online and offline contexts.